PSYCHOMETRIC VALIDATION OF A DIAGNOSTIC TRIGONOMETRY TEST APPLIED TO UNIVERSITY STUDENTS - Márquez, Dalia Imelda Castillo; Cuesta, Richard Gutiérrez; López, Georgina Elizabeth Partida; Flores, Alan Roberto Figueroa; Dávalos, Arturo Javier Gómez; Méndez, Juan Luis Hernández (Seven Editora, 2026)
The present study aimed to analyze the psychometric properties of a diagnostic trigonometry test designed for university students. The study design was quantitative, non-experimental, cross-sectional, and instrumental. A total of 50 higher education students participated, selected through non-probabilistic purposive sampling. The instrument consisted of 10 dichotomous items (1 = correct, 0 = incorrect) assessing trigonometric functions, identities, and triangle solving. The difficulty index (p), corrected point-biserial correlation (rₚᵦ), and Cronbach’s alpha coefficient (α) were calculated. The results indicated acceptable reliability (α = 0.748). Item analysis showed that most items had moderate difficulty and adequate discrimination; however, Item 8 showed virtually no discrimination (rₚᵦ = 0.001), while Items 3 and 7 presented low discrimination. It is concluded that the instrument has satisfactory psychometric properties as a diagnostic tool, although it requires revision of three specific items to improve its technical quality. The findings provide useful empirical evidence for decision-making in introductory university-level trigonometry instruction.